2004
DOI: 10.1074/jbc.m400161200
|View full text |Cite
|
Sign up to set email alerts
|

Proximal and Distal Sequences Control UV Cone Pigment Gene Expression in Transgenic Zebrafish

Abstract: The molecular basis of cone photoreceptor-specific gene expression is largely unknown. In this study, we define cis-acting DNA sequences that control the cell type-specific expression of the zebrafish UV cone pigment gene by transient expression of green fluorescent protein transgenes following their injection into zebrafish embryos. These experiments show that 4.8 kb of 5 -flanking sequences from the zebrafish UV pigment gene direct expression specifically to UV cones and that this activity requires both dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…It was shown that the adjacent upstream regions of RH2-1 and RH2-3 of 10.5 and 8 kb, respectively, failed to drive the GFP reporter expression (14). These negative results were confirmed for the four RH2 opsin genes by injecting the GFP reporters conjugated to their adjacent upstream regions of 7.3, 2.8, 2.6, and 6.7 kb in RH2-1, RH2-2, RH2-3, and RH2-4, respectively, into zebrafish embryos.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that the adjacent upstream regions of RH2-1 and RH2-3 of 10.5 and 8 kb, respectively, failed to drive the GFP reporter expression (14). These negative results were confirmed for the four RH2 opsin genes by injecting the GFP reporters conjugated to their adjacent upstream regions of 7.3, 2.8, 2.6, and 6.7 kb in RH2-1, RH2-2, RH2-3, and RH2-4, respectively, into zebrafish embryos.…”
Section: Resultsmentioning
confidence: 99%
“…3 g and h). The SWS1up854bp is incapable of inducing gene expression in the retina (14). The krt8up564bp induces gene expression specifically in the epithelial tissues, but not in the retina, and has been used for enhancer trapping as a basal promoter (19).…”
Section: A Distal Regulatory Region Rh2-lcr Was Found In the Rh2-pamentioning
confidence: 99%
See 1 more Smart Citation
“…At 7-8 days post-fertilization (dpf), the percentage of the eyes with GFP signal among all the eyes examined was taken as a measure of the efficiency of the transgene expression. The GFP-positive eyes were further distinguished into three levels by the number of GFP-positive cells per eye as follows: ϩϩϩ (Ͼ50 cells), ϩϩ (5-50 cells), and ϩ (1-4 cells), as in previous studies (30,31). Whereas the ϩϩϩ and ϩϩ were taken as a significant sign of the expression induction, the ϩ was not.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry-Immunostaining was carried out for whole-mount retinas of 5-8 dpf larvae or adult retinal sections by following Luo et al (30). Antibodies against zebrafish opsins raised in rabbits were provided by T. Vihtelic and D. Hyde (University of Notre Dame, South Bend, IN) (24) and were used to stain cone photoreceptor cells.…”
Section: Methodsmentioning
confidence: 99%